Identification of gaps for implementation science in the HIV prevention, care and treatment cascade; a qualitative study in 19 districts in Uganda - Bajunirwe, Francis; Tumwebaze, Flora; Abongomera, George; Akakimpa, Denis; Kityo, Cissy; Mugyenyi, Peter N. (BMC research notes, 2016)
Over the last 20 years, countries in sub Saharan Africa have made significant strides in the implementation of programs for HIV prevention, care and treatment. Despite, the significant progress made, many targets set by the United Nations have not been met. There remains a large gap between the ideal and what has been achieved. There are several operational issues that may be responsible for this gap, and these need to be addressed in order to achieve the targets. Therefore, the aim of this study was to identify gaps in the HIV prevention, care and treatment cascade, in a large district based HIV implementation program. We aimed to identify gaps that are amenable for evaluation using implementation science, in order to improve the delivery of HIV programs in rural Uganda.We conducted key informant (KI) interviews with 60 district health officers and managers of HIV/AIDS clinics and organizations and 32 focus group discussions with exit clients seeking care and treatment for HIV in the 19 districts. The data analysis process was guided using a framework approach. The recordings were transcribed verbatim. Transcripts were read back and forth and codes generated based on the framework.Nine emerging themes that comprise the gaps were identified and these were referral mechanisms indicating several loop holes, low levels of integration of HIV/TB services, low uptake of services for PMTCT services by pregnant women, low coverage of services for most at risk populations (MARPs), poor HIV coordination structures in the districts, poor continuity in the delivery of pediatric HIV/AIDS services, limited community support for orphans and vulnerable (OVC’s), inadequate home based care services and HIV services and support for discordant couples. The themes indicate there are plenty of gaps that need to be covered and have been ignored by current programs.Our study has identified several gaps and suggested several interventions that should be tested before large scale implementation. The implementation of these programs should be adequately evaluated in order to provide field evidence of effectiveness and replicability in similar areas.
Keywords: Gaps, Implementation science, HIV, Qualitative, Uganda, Districts